El desemparo como argumento : mujeres en defensa de padres, esposos e hijos ante la ley de expulsión de españoles de 1829 en México - María Graciela León Matamoros (Les Cahiers ALHIM)
Nearby 1827 were promulgated some laws and dispositions against the spaniards-peninsulares, and the most important was the Expulsion Law promulgated in December of 1827. Later on, in 1828, this Law was considered not as hard as it should be. Some exceptions were marked in the process for the peninsulares’ expulsion, for example, about those Spanish men who were married with Mexican women and with children born in Mexico. The expulsion was not effective, and due to complains and protests of different social sectors, it was established a second Law, in March of 1829, and the exceptions were more limited. The 1829 Expulsion Law did not allow Spanish lived in the country even if they were married Mexican women or had had children. The banishment threatening affected husbands, fathers, sons, etc., and therefore a lot of women protested in opposition to this kind of laws. They sent letters to the Mexican president, Vicente Guerrero, and argued many reasons about the benefits of their relatives’ permanence in México and the consequences of their banishment. As a result of the women involvement in this process, they succeed in the most of their letters